Dissemination of Religious Moderation for Students in Strengthening Inclusive Islam at Pesantren of Jekulo Kudus - Moh Muhtador; Shofaussamawati (LP2M of Institute for Research and Community Services - UIN Walisongo, 2025)
The issue of religious moderation is a government programme aimed at countering narratives, attitudes, and actions of intolerance. However, this programme is not widely disseminated in communities such as Islamic boarding schools. Activities carried out at the Jekulo Kudus Islamic Boarding School aim to empower students to promote religious moderation and tolerance. The aim is to reveal the lack of study of the works of Indonesian scholars in various Islamic boarding schools, while the works of Middle Eastern scholars still dominate. The method used is PAR, which directly involves students in studying the book Risalah Tawhid by Mbah Hasyim Asy'ari and the book Faidhul Rahman by Mbah Shaleh Darat. The findings indicate that students remain unfamiliar with Indonesian scholars, possess minimal knowledge about the moderate teachings of Nusantara scholars, and have a partial understanding of the teachings of religious moderation, both from the ministry and from religious perspectives. This article contributes to illustrating that santri need to be introduced to and taught the works of Nusantara scholars.